Style of the Nid?' Language: A Study of its Structure and Function in the Interpretation of the Qur'an - Lukman Saraji; Muhammad Yusuf; Mohammad Harjum (Universitas Muhammadiyah Palu, 2025)
This study discusses the concept of nid?' (call or call) in the Qur'an as a form of language style that is full of meaning and purpose of communication. This study departs from the view of Quraish Shihab and Fazlurrahman that the Qur'an has a breadth of meaning that can be studied from various points of view, including linguistic and rhetorical aspects. The Nid?' in the Qur'an not only serves as a summoner, but also conveys da'wah messages, warnings, invitations, and even prohibitions and questions. This study classifies nid?' into three main forms: nid?' '?m (general appeal), nid?' kh?? (a special appeal to a particular group), and nid?' lil-asykh?? (a call to a specific individual). In addition, the lexical and terminological meaning of nid?', the types of nid?' letters, as well as the essential meaning of majazi in its use are also discussed. With an approach to linguistic analysis and interpretation, this study confirms that the style of nid?' language in the Qur'an contains a strategic theological, pedagogical, and psychological content in conveying divine messages to mankind in various contexts.